Japanese perspectives on transformative travel experience: humility, limitations, and dark tourism - Nakajima, Miho; Oguchi, Takashi (Frontiers in Psychology, 2025)
IntroductionAlthough prior research has suggested that cultural background may influence the nature of transformative travel experiences, empirical studies conducted outside Western contexts remain limited. This study aims to explore how Japanese travelers experience transformative travel and to examine the cultural specificity of such experiences.MethodsA cross-sectional online survey was conducted with 864 Japanese adults, including both individuals who had experienced transformative travel and those who had not. Participants provided open-ended responses and completed the Japanese version of the Transformation Scale, which was examined for its validity and factor structure.ResultsThe findings indicated that Japanese travelers experienced transformative travel triggered by factors similar to those identified in Western studies, such as exposure to different values and reflective moments during travel. However, culturally distinctive outcomes also emerged, including enhanced humility and a deeper recognition of personal limitations. In addition, visits to destinations associated with dark tourism were found to promote transformative travel experiences. The factor analysis of the Japanese version of the Transformation Scale revealed a structure that differed from the original, suggesting cultural differences in how personal transformation is perceived and expressed.DiscussionThese findings highlight the influence of cultural context on the nature and outcomes of transformative travel. The study contributes to a broader understanding of transformative travel experiences by revealing culturally specific elements among Japanese travelers and by validating a culturally adapted measurement scale. Future research should continue to explore cross-cultural variations in transformative travel in order to develop more inclusive theoretical frameworks.